Treatment of Paecilomyces variotii pneumonia with posaconazole: case report and literature review. Issue 12 (12th July 2016) - Feldman, Ryan; Cockerham, Leslie; Buchan, Blake W.; Lu, Zouyan; Huang, Angela M.
Summary: The fungi Paecilomyces variotii is a potential pathogen in immunocompromised and immunocompetent patients. Their rare association with clinical disease results in scarce literature regarding susceptibility and treatment. Here, we discuss a case involving successful treatment of probable P. variotii pneumonia with posaconazole after treatment failure with voriconazole. The current literature related to antifungal susceptibility profiles, microbiological identification methods and clinical management of infections caused by this organism is also reviewed.